1996
DOI: 10.3109/13816819609057111
|View full text |Cite
|
Sign up to set email alerts
|

G106R rhodopsin mutation is also present in Spanish ADRP patients

Abstract: A large family affected with autosomal dominant retinitis pigmentosa (ADRP) with a sectorial phenotype showed a previously described (G to A) mutation in the rhodopsin gene resulting in the substitution of a glycine residue by an arginine in codon 106 of rhodopsin. This mutation shows some unusual characteristics, such as initial pathology of the inferior retina, superior visual field with normal disc and retinal vessels, and ERG findings that show a modest reduction in both cone and rod amplitudes with normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Preferential degeneration of the inferior retina has been reported in multiple families with other mild phenotypes, including patients with the Pro23His mutation. 7,18,[23][24][25][26]28,29 However, none of our Pro23Ala group demonstrated diffuse disease, which can sometimes be *Normal indicates healthy subjects; Pro23Ala, patients with proline to alanine substitution at codon 23; and Pro23His, patients with proline to histine substitution at codon 23. †The values in parentheses are the amplitudes in microvolts before transformation to a square root.…”
Section: Molecular Resultsmentioning
confidence: 93%
“…Preferential degeneration of the inferior retina has been reported in multiple families with other mild phenotypes, including patients with the Pro23His mutation. 7,18,[23][24][25][26]28,29 However, none of our Pro23Ala group demonstrated diffuse disease, which can sometimes be *Normal indicates healthy subjects; Pro23Ala, patients with proline to alanine substitution at codon 23; and Pro23His, patients with proline to histine substitution at codon 23. †The values in parentheses are the amplitudes in microvolts before transformation to a square root.…”
Section: Molecular Resultsmentioning
confidence: 93%
“…As compared to classic RP, sector RP is considered to be a less severe disease with subnormal ERG and visual field defects that correspond to the affected sectors [ 13 , 14 ]. In fact, it has been reported that sector RP is caused by a number of RHO mutations, including p.T4K [ 38 ], p.N15S [ 39 41 ], p.T17M [ 33 , 42 ], p.P23H [ 10 ], p.T58R [ 12 ], p.N78I [ 43 ], and G106R [ 11 , 25 , 44 ]. To the best of our knowledge, there have been nine RHO mutations reported in the Japanese adRP population [ 20 , 22 25 , 32 , 33 , 41 ], with detailed phenotypes described in five (p.N15S, p.T17M, p.G106R, p.E181K, and p.P347L) out of the nine mutations [ 20 , 23 25 , 32 , 33 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 summarizes the clinical features that were described for the genotype-phenotype correlations of the seven Japanese adRP families (including our families) with the seven RHO mutations (p.N15S, p.T17M, p.G106R, p.W126L, p.E181K, p.A346P, and p.P347L). Interestingly, patients with five other mutations (p.N15S [ 39 41 ], p.T17M [ 33 , 42 ], p.G106R [ 11 , 25 , 44 ], p.A346P [ 34 ], and p.P347L [ 5 , 32 , 45 ]) were found to have phenotypes that were similar to Japanese and other ethnic groups, although the clinical phenotypes for two other mutations (p.W126L and p.E181K [ 20 , 21 , 46 ]) could not be sufficiently evaluated [ 5 , 11 , 20 , 21 , 25 , 32 – 34 , 39 42 , 44 46 ]. These findings suggest that the location of each missense mutation is important for the purpose of predicting a diagnosis of either classic or sector RP and that there is a similarity of phenotypes between Japanese and other ethnic group RP patients who have identical RHO mutations.…”
Section: Discussionmentioning
confidence: 99%